(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Within linguistics a word class is defi ned in grammatical terms as a set of words that exhibit the same syntactic properties. In this paper the aim is to argue that the meanings of different word classes can be given a cognitive grounding. It is shown that with the aid of conceptual spaces, a geometric analysis can be provided for the major word classes. A universal single-domain thesis is proposed, saying that words in all content word classes, except for nouns, refer to a single domain.